KONTRIBUSI PENGALAMAN PRAKTIK KERJA INDUSTRI, MOTIVASI MEMASUKI DUNIA KERJA, DAN PRESTASI BELAJAR PEMASARAN TERHADAP KESIAPAN KERJA SISWA PROGRAM KEAHLIAN PEMASARAN SMK NEGERI 1 REMBANG KABUPATEN PURBALINGGATAHUN PELAJARAN 2016/2017 - -, Puji Hastuti -; -, Soetarno Joyoatmojo -; -, Hery Sawiji - (Prosiding Seminar Pendidikan Ekonomi dan Bisnis, 2017)
ABSTRACTÂ The purpose of this study were (1) to determine the contribution of working practices of industrial and motivation to enter the workforce to the learning achievement of marketing together (simultaneously), (2) To determine the contribution of working practices of industrial and motivation to enter the workforce to learning achievement marketing individually (partial). (3) to determine the contribution of the practice of industrial work, motivation to enter the world of work, and learning achievement of marketing on the readiness of students work together (simultaneously), (4) To determine the contribution of the practice of industrial work, motivation to enter the world of work, and learning achievement marketing the readiness of the students work individually (partial).Based on the analysis of data to test the hypothesis, it can be concluded there is a significant contribution to the practice of industrial work and motivation to enter the workforce with the readiness of students work together (simultaneously), a significant difference between the practice of industrial employment and motivation of entering the world of work the readiness of the students work individually (partial), there is a significant contribution to the practice of industrial work, motivation to enter the world of work, and learning achievement of marketing on the readiness of students work together (simultaneously), a significant difference between the practice of industrial employment , motivation to enter the world of work, and learning achievement of marketing on the readiness of the students work individually (partial). Variable industry work practices and motivation to enter the workforce affect the learning achievement of marketing, it can be calculated the indirect effect of both variables on the readiness of the students work. Variable industry work practices (X1) to the job readiness of students (Y2) through marketing learning achievement (Y1) is: 0.336 x 0.162: 0.054432. Enter the job motivation variable (X2) on the job readiness of students (Y2) through marketing learning achievement (Y1) is: 0.473 x 0.162: 0.076626. The net effect of variable industrial working practices on the readiness of students work is: 0.169 + 0.054432: 0.223432. Total variable influence motivation to enter the workforce with the readiness of the students work is: 0.163 + 0.076626: 0.239626.Keywords: working practices of industrial, motivation to enter the workforce, learning achievement of marketing, readiness of the students workÂ